Emissions Trading and Promotion of Renewable Energy: We Need Both - Claudia Kemfert; Jochen Diekmann (Weekly Report, 2009)
Emissions trading and the promotion of the use of energy from renewable sources are key elements of German and European energy and climate policy. However, some critics oppose a targeted promotion of renewable energy, arguing in particular that this is ineffective or even damaging in conjunction with European emissions trading. Yet upon closer examination, the coexistence of emissions trading and promotion of renewable energy is not only possible, it is essential-provided the interactions between them are taken into account. It would be a mistake to discontinue the promotion of renewable energy. Quite to the contrary: A commitment to the continuation and further development of subsidy measures is necessary so that renewable energy-alongside increased energy efficiency-can furnish the foundation for a sustainable energy supply.
Keywords: Q2; Q4; Q5; 330; Renewable Energy; Emissions Trading; Policy Mix